Enhancing Interest and Achievement: Development of Smartbox Learning Media in Pancasila Education - Chintya, Chintya Asti Halizha; Fathurrahman, Mohammad (Edukasi, 2025)
This study aimed to develop Smartbox learning media to enhance student interest and learning achievement in Pancasila Education for third-grade elementary students. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted at SD Negeri Salamsari, involving 30 third-grade students as participants. Data were collected through expert validation forms, student questionnaires on learning interest, pre-test and post-test assessments, classroom observations, and teacher interviews. The media received high validity scores from experts: 93.3% from media experts and 97.5% from material experts. After implementation, student motivation and participation increased significantly, and the average academic scores improved from 58 in the pre-test to 82 in the post-test. These results suggest that the Smartbox is an effective learning tool for transforming abstract Pancasila concepts into engaging, concrete learning experiences that support both student motivation and academic achievement.